The Impacts of Cloud Manufacturing on the Supply Chain - Alrihawi, Abdulla (2016)
Cloud manufacturing is a recent technique used in manufacturing sector to fulfill the agility of the fluctuation between supply and demand. This paper focuses on the impact of cloud manufacturing on supply chain, and how the impacts vary from one industry to another due to different variable factors. The research method used in this paper is consist of a literature review on the concept of cloud computing, cloud manufacturing and the supply chain characteristics. Followed by a comparison made among different scenarios where the performance of cloud manufacturing was assessed in different supply chains. The findings from this research provides an evidence about that not only different supply chains will have a different impacts by cloud manufacturing but also different condition results different impacts in the same supply chain. The main conclusion drawn from this study is that cloud manufacturing generally has a significant positive impact on the supply chains that benefit as much as possible from its features. This dissertation recommends a further studies on classifying supply chains with similar major variable factors in order to have a coherent understanding about cloud manufacturing impacts in similar categories.